Proceedings of the 12th Reinventing Space Conference - Hatton, Scott (Springer International Publishing : Imprint: Springer, 2017)
The 2014 Reinventing Space conference presented a number of questions in the context of a constantly innovating space industry, from addressing the future of global cooperation, investigating the impact of cuts in US government spending on the private space sector, and probing the overall future of the commercial launch sector. Space tourism and new technology promise the revival of interest in space development (the Apollo Era was the first period of intense space activity and growth). The need to create dramatically lower cost, responsive and reliable launch systems and spacecraft has never been more vital. Advances in technology are allowing smaller and cheaper satellites to be orbited - from cubesats to nanosatellites to femtosatellites. Thanks to more efficient new launch possibilities, low cost access to space is becoming ever more achievable. Commercial companies and countries are targeting the industry with new funding. Organised by the British Interplanetary Society, the presentations at this conference thoroughly address these challenges and opportunities.